Begging abroad in Sweden: An interview study. (17th August 2020) - Wagman, Petra; Johansson, Ann; Fristedt, Sofi
Abstract: Background : The occurrence of begging by poor people from other countries in the European Union (EU) is now common in Scandinavia. They have a challenging life, but there is little knowledge about their own perceptions of their stay abroad. Aim : To explore the experiences of EU citizens begging in Sweden. Material : A descriptive design was used. Data were gathered through individual interviews conducted in Romanian and translated into Swedish. These were analysed using conventional content analysis. Participants were 20 EU citizens aged 19–64 years with experience of begging in Sweden. Results : The identified main category, "A hard time abroad to improve one's life", contained four categories – "Endurance is required to make a living"; "Exposed to others' attitudes and kindness"; "Handling being away"; and "A better life is the driving force". Conclusions and significance : EU citizens who beg face occupational injustice, spending many hours in non-preferred activity of begging and with few leisure activities, although no generalizations can be drawn based on this study. The importance of a friendly attitude and environmental support when abroad was also shown. Since occupational justice is within the scope of occupational therapy, occupational therapists have the skills to contribute in collaboration with others.